Impact of chest imaging quality on the diagnosis of the usual interstitial pneumonia pattern: a hub and spoke study. Issue 6 (27th June 2019) - Sgalla, Giacomo; Larici, Anna Rita; Re, Antonina; Farchione, Alessandra; Cicchetti, Giuseppe; Calandriello, Lucio; Comes, Alessia; Golfi, Nicoletta; Iovene, Bruno; Varone, Francesco; Manfredi, Riccardo; Richeldi, Luca
Accurate diagnosis of idiopathic pulmonary fibrosis (IPF) is essential to ensure prompt initiation of appropriate treatment and enrolment in clinical trials. According to current international guidelines [1], in the appropriate clinical context the identification of the usual interstitial pneumonia (UIP) pattern on chest high-resolution computed tomography (CT) allows a confident diagnosis of IPF. Patients referred to tertiary centres for suspected interstitial lung disease (ILD) may provide CT images that do not fulfil recommended scanning protocols [1], therefore triggering the execution of another CT. However, the impact of suboptimal technical quality on the identification of the UIP pattern by thoracic radiologists is unknown. We assessed the quality of chest CT scans performed in the context of an ILD network including a tertiary ILD centre (hub) and the affiliated centres (spokes), and the impact on the identification of the UIP pattern. CT technical quality affects the recognition of the UIP pattern by thoracic radiologists. Optimal CT scanning protocols should be implemented in spoke centres to speed up the diagnostic work-up of IPF, reducing costs and further radiation exposure. http://bit.ly/2Jo4EqQ